THE ROLE OF SOME REVERSE LOGISTICS ACTIVITIES IN ENHANCING SUSTAINABLE COMPETITIVE ADVANTAGE: AN EXPLORATORY STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT THE BADOUSH CEMENT FACTORY IN NINEVEH PROVINCE - Omar S. Abdullah (Scholars Digest Publishing, 2024)
This research aims to measure and identify the role of certain reverse logistics activities in enhancing the sustainable competitive advantage of the studied factory. This, in turn, reflects in improved employee performance, increased productivity, and boosted morale among individuals working in the environment, leading to the enhancement of the sustainable competitive advantage of the studied plant. This, in turn, strengthens the sustainable competitive advantage of the factory under study. The research problem is represented by the fact that the workplace suffers from low productivity due to the use of traditional tools and methods, which have a negative effect on the factory and its employees. To address this problem, the study adopts the approach of reverse logistics activities to overcome the weaknesses in the material resources used in the work environment, thereby enhancing sustainable competitive advantage. A questionnaire was used as the primary tool for data collection in the researched field, and the sample comprised employees at the (Badosh Cement Factory) in Nineveh Governorate, specifically in the city of Mosul. Data were analyzed, leading to a set of conclusions based on the results. The research also presents a series of recommendations that benefit the studied factories.
Keywords: Reverse logistics activities, sustainable competitive advantage.